The land before time X : the great migration (Universal City, Calif : Universal Home Entertainment, 2003)
Littlefoot has a vivid dream in which he imagines travelling to a place where there are many of his kind, and when he tells the story to his grandparents, they take it as a sign to set out and find this mysterious place. After days of travel they do indeed discover a new world where longneck dinosaurs are plentiful, including one they never expected to see -- Bron, Littlefoot's father, who went missing before he was born. While Littlefoot is thrilled to be reunited with his father, now he must choose if he should stay with Bron, or the grandparents who have cared for him for years.